Prognostic value of tumour-infiltrating lymphocytes in small HER2-positive breast cancer. (December 2017) - Criscitiello, Carmen; Bagnardi, Vincenzo; Pruneri, Giancarlo; Vingiani, Andrea; Esposito, Angela; Rotmensz, Nicole; Curigliano, Giuseppe
Abstract: Background: The standard treatment for patients with small, node-negative, human epidermal growth factor receptor type 2 (HER2)–positive breast cancer (BC) is still controversial. Our aim was to assess the prognostic role of tumour-infiltrating lymphocytes (TILs) in patients with stage pT1a–b HER2-positive BC. Patients and methods: Haematoxylin and eosin slides from node-negative, pT1a–b HER2-positive BC surgical specimens were retrieved from pathology archives to assess TILs and their association with outcome. Results: TILs were evaluated in 205 patients with HER2-positive, pT1a–b tumours, who underwent breast surgery between 1997 and 2009 at the European Institute of Oncology. At a median follow-up of 11 years, we did not observe any association between the presence of TILs, either assessed as a continuous or dichotomous variable (<50 versus ≥ 50%), and outcome. Within the subgroup of patients with pT1a tumours who did not receive any adjuvant therapy (36/97 patients), the rate of disease-free survival events was lower in lymphocyte-predominant BC (LPBC) as compared with non-LPBC patients (p = 0.066). Conclusions: TILs cannot be used as a prognostic biomarker in pT1a–b HER2-positive BC. Additional biomarkers are needed for selecting patients with stage I HER2-positive BC who candidate to adjuvant therapy de-escalation. Highlights: We assessed the prognostic role of tumour-infiltrating lymphocytes (TILs) in patients with stage pT1a–b human epidermal growth factor receptor type 2 (HER2)–positive breast cancer (BC). At a median follow-up of 11 years, we did not observe any association between the presence of TILs, either and outcome.